A Practical Fitting Method Involving a Trade-Off Decision in the Parametrization Procedure of a Thermodynamic Model and Its Repercussion on Distillation Processes
The design of processes containing information on phase equilibria must be carried out through a series of steps, experimentation $ verification $ modeling $ simulation. Each of these steps should be rigorously performed to guarantee a good representation of the behavior of the system under study, whose adequate modeling could be used to simulate the corresponding process. To carry out the different previous tasks, two representative systems, extracted from known database, are used. The quality checking of experimental data series is certified through several thermodynamic consistency methods. The modeling is done by applying a multiobjective optimization procedure, which allows to define a solution front (Pareto front) for different sub-models that are established in this work. The fitness of trade-off solutions, obtained from the efficient front, on the design of distillation processes is analyzed through a simulation.